Cross-border spatial development in Bavaria: Starting point, current challenges and conceptual debates - Tobias Chilla; Franziska Sielker (Cross-border spatial development in Bavaria: Dynamics in cooperation - Potentials of integration, 2022)
This introductory article has three goals. First, it briefly introduces Bavaria's border areas. Second, the paper introduces three institutional and political perspectives to explain the governance arrangements and processes in the border areas, namely institutional ambiguity, reterritorialisation and multi-level mismatches. Further, the article discusses current developments from a functional perspective by reflecting on processes of convergence, metropolisation and 'tunnel effects'. Third, the article outlines the implications of the results for Bavarian federal state planning.
urn:nbn:de:0156-41580182; hdl:10419/253270; https://econpapers.repec.org/RePEc:zbw:arlabe:34
Keywords: 710; Cross-border spatial planning; governance; cohesion; Czech Republic; Austria